2018
DOI: 10.12715/har.2018.7.12
|View full text |Cite
|
Sign up to set email alerts
|

Psychoneuroendocrine immunology (PNEI) and longevity

Abstract: Psychoneuroendocrineimmunology (PNEI) is the science which studies the interactions between psychological, neural, endocrine and immunological processes. The concept of the PNEI system was developed in the seventies and eighties through the discoveries of the interaction between immune system and molecules with neuroendocrine activity targeting multiple organs; the interdependence between immunological, psychological and neuroendocrine mechanisms has been elucidated through several studies subsequently. PNEI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…According to recent works, psychological traits seem to share a common pathogenic mechanism typical of increased mucosal inflammation, metabolic parameters and proinflammatory status (Mancini et al, 2020 ). In line with this, an increasing number of studies are equating psychosocial factors (depression, anxiety, hostility, social isolation) to biological factors (smoking, hypercholesterolemia, hypertension, obesity, diabetes) in the pathogenesis of several diseases (Attilio et al, 2018 ). In the oncological field, a meta-analysis carried out on 165 controlled studies showed that stress-prone personality or unfavorable coping styles and negative emotional responses are related to an increased incidence of cancer, a worse prognosis and an increase in mortality (Chida et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to recent works, psychological traits seem to share a common pathogenic mechanism typical of increased mucosal inflammation, metabolic parameters and proinflammatory status (Mancini et al, 2020 ). In line with this, an increasing number of studies are equating psychosocial factors (depression, anxiety, hostility, social isolation) to biological factors (smoking, hypercholesterolemia, hypertension, obesity, diabetes) in the pathogenesis of several diseases (Attilio et al, 2018 ). In the oncological field, a meta-analysis carried out on 165 controlled studies showed that stress-prone personality or unfavorable coping styles and negative emotional responses are related to an increased incidence of cancer, a worse prognosis and an increase in mortality (Chida et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…), according to which the biological functions of the body are interconnected, ensuring a homeostatic balance. The disruption of this equilibrium may lead to the development of diseases [73]. The homeostatic balance can be re-established through low-dose medicine (LDM), an approach based on the oral administration of biological molecules at concentrations close to physiological levels, in a range between 10 −9 (nanograms/mL) and 10 −15 M (femtograms/mL) [74].…”
Section: The Foundation Of Oral Low-dose Cytokine Treatmentsmentioning
confidence: 99%
“…The neuroendocrine-immune interactions (NEIIs) model establishes that there is a permanent coexistence between the nervous, endocrine, and immune systems. NEIIs modulate various physiological processes, among them the response to stress, a condition that, if prolonged, can culminate in the development of MDD 4 . The presence of chronically stressful stimuli generates the release of IL-1, IFN-y, TNF-α, and IL-6, which stimulate the neuroendocrine system by inducing a response in which more cytokines are released by microglia.…”
mentioning
confidence: 99%